Comorbidities, Gender, and Race in the Severity of COVID-19 - Obih, Patience O; Howard, Elizabeth; Innocent-Itua, Ijeoma; Olet, Susan (British Journal of Healthcare and Medical Research, 2025)
Objective: COVID-19 pandemic claimed a lot of lives. Comorbidities have been suggested to drive the number of patients who suffered from COVID-19. This study was conducted retrospectively to examine how comorbidities like diabetes, hypertension, and factors like vaccination, race and gender impacted COVID-19 in patients admitted to the hospital (in-patient services) with a COVID-19 diagnosis. Method: A retrospective cohort study of 17,624 adult patients diagnosed with COVID-19 and admitted to in-patient services at Ochsner Health, between March 1, 2020 and March 31, 2022 was conducted. All data, including demographics, comorbidities, laboratory results, COVID-19 vaccination status, and severity of disease were collected from the electronic health record and analyzed. Result: In the unadjusted analysis, diabetes and hypertension were statistically significant predictors of major/extreme SOI (p < 0.0001) and ROM (p < 0.0001). Age and vaccination status were significant (p < 0.0001), but the strength of association was weak: as age increases, severity of illness (SOI) increases (RR=1.00(1.00-1.00)). Length of hospital stay was significantly longer for patients with diabetes after controlling for age and prior vaccination status (p < 0.0001). This study also shows that patients with diabetes or hypertension comorbidities were more likely to be vaccinated prior to admission than those without the comorbidity. Conclusion: Our study showed that patients with diabetes or hypertension comorbidities were more likely to be vaccinated prior to admission than those without the comorbidity. However, having these diagnoses may worsen the outcome of COVID-19 infection. Diagnosis with prior diabetes or hypertension was marginally associated with major or extreme severity of illness [RR(95% CI)= 1.02(1.01-1.03) and RR(95% CI)= 1.01(1.01-1.02)] and risk of mortality [RR(95% CI)= 1.05(1.04-1.07) and RR(95% CI)= 1.03(1.02-1.04)] compared to minor or moderate risk.